The German attack on the Witboois at Hornkranz, Namibia, April 1893 - van Rooyen, Petrus Hendrik (Scientia Militaria - South African Journal of Military Studies, 2021)
For many, when the Namibian struggle for liberation is mentioned, the struggle for liberation by the South West Africa People’s Organization (SWAPO) comes to mind. For others to the south of Namibia, it recalls images of a border war and incursions into Angola to ‘stop SWAPO’, the latter seen as a communist pawn directed and armed by the Soviet Union and Cuba. More than that is seldom asked about or seen in terms of the bigger historical collage. The brutal era of German colonisation is habitually overlooked. The Namibians’ struggle for liberation lasted nearly a century. It started through, for example, the massacre or battle, depending on your view, in April 1893. This previously poorly researched story about which little is written is told in this article.